2015
DOI: 10.1002/cphc.201500563
|View full text |Cite
|
Sign up to set email alerts
|

Environment‐Sensitive Behavior of DCNP in Solvents with Different Viscosity, Polarity and Proticity

Abstract: A pyrazoline derivative, 3-(1,1-dicyanoethenyl)-1-phenyl-4,5-dihydro-1H-pyrazole (DCNP), is studied by using optical spectroscopy methods in several solvents at room and at low temperatures. The DCNP molecule reveals a complex photophysics behavior, which is sensitive to solvent polarity, proticity, temperature and viscosity and arises from the presence of two rotational degrees of freedom of the dicyanovinyl group--the torsion around the double C=C bond and the s-trans-s-cis isomerization around the single C-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
14
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 42 publications
2
14
0
Order By: Relevance
“…Experimental studies and previous quantum mechanical calculations have shown that DCNP presents a photophysics, which depends on the polarity and viscosity of the environment. [ 9 ] A brighter fluorescence is found for nonpolar solvents and in more viscous environments, and ASE has been observed in a poly(methyl methacrylate) matrix, [ 10 ] suggesting DCNP as suitable dye for use in rigid matrices. In fact, DCNP presents the typical characteristics of a potential twisted‐internal‐charge‐transfer (TICT) system: an electron donor group (benzene ring), an electron attractor group (cyan groups), and a network of conjugated bonds that delocalize the electronic density, connecting the two subunits.…”
Section: Resultsmentioning
confidence: 99%
“…Experimental studies and previous quantum mechanical calculations have shown that DCNP presents a photophysics, which depends on the polarity and viscosity of the environment. [ 9 ] A brighter fluorescence is found for nonpolar solvents and in more viscous environments, and ASE has been observed in a poly(methyl methacrylate) matrix, [ 10 ] suggesting DCNP as suitable dye for use in rigid matrices. In fact, DCNP presents the typical characteristics of a potential twisted‐internal‐charge‐transfer (TICT) system: an electron donor group (benzene ring), an electron attractor group (cyan groups), and a network of conjugated bonds that delocalize the electronic density, connecting the two subunits.…”
Section: Resultsmentioning
confidence: 99%
“…This observation is likely connected with the strong push−pull character of the Lemke's chromophore derivative which in weak polar environment, such as DCM, could effectively dissipate excitation energy through the twist of dicyanoethenyl group. 29,38 Excitation and emission spectra of the investigated layered materials are shown in Figure 1. Ant-PMMA shows broad excitation bands, with maximum at λ ex = 520 nm.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…There is a growing family of polarized molecular systems in which optical excitation to the 1 LE state can significantly increase the dipole moment of the system . Among these, a class of highly polarized molecular dyads composed of two coumarin moieties linked in a (donor–acceptor)–linker–(donor–acceptor) (DA‐L‐DA) orientation, recently studied by us, is particularly interesting.…”
Section: Introductionmentioning
confidence: 99%